PENGEMBANGAN BAHAN AJAR “LESTARI” BERBASIS POTENSI LOKAL BAGI SISWA KELAS IV SD - Ervawaty Ervawaty; Fathul Zannah; Tazkiyatunnafs Elhawwa (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The background of this research is based on the minimal integration of the richness of local potential of Katingan Regency in national textbooks, so that the learning of science at SDN 4 Kasongan Lama becomes less contextual for fourth grade students. The focus of the research problem is directed at the development and testing of the validity, effectiveness, and efficiency of integrated thematic teaching materials entitled "LESTARI". The research procedure applies the Research and Development method through the ADDIE model which includes the stages of needs analysis, material structure design, prototype development, classroom implementation, and comprehensive evaluation. The validation results from material experts, media, and education practitioners indicate that this product is in the category of very feasible for use. Quantitative findings prove a significant increase in learning achievement, where the average student score jumped from 61.46 to 80.21. Statistical analysis through paired sample t-test produces a t-value of 19.25 which exceeds the t-table of 2.069, supported by the acquisition of an effect size of 3.93 which is classified as very large. The main conclusion confirms that the "LESTARI" teaching material is proven to be valid, effective, and efficient in supporting meaningful environment-based learning. The use of local content such as peat swamp ecosystems and Dayak culture not only optimizes cognitive achievement, but also successfully internalizes environmental care and ecological awareness in students from an early age in a sustainable, systematic, and holistic manner for the future sustainability of the Katingan environment.ABSTRAKLatar belakang penelitian ini berpijak pada minimnya integrasi kekayaan potensi lokal Kabupaten Katingan dalam buku teks nasional, sehingga pembelajaran IPAS di SDN 4 Kasongan Lama menjadi kurang kontekstual bagi siswa kelas IV. Fokus masalah penelitian diarahkan pada pengembangan serta pengujian validitas, efektivitas, dan efisiensi bahan ajar tematik terpadu berjudul "LESTARI". Prosedur penelitian menerapkan metode Research and Development melalui model ADDIE yang mencakup tahapan analisis kebutuhan, perancangan struktur materi, pengembangan prototipe, implementasi kelas, hingga evaluasi menyeluruh. Hasil validasi dari para ahli materi, media, dan praktisi pendidikan menunjukkan bahwa produk ini berada pada kategori sangat layak untuk digunakan. Temuan kuantitatif membuktikan adanya peningkatan prestasi belajar yang signifikan, di mana nilai rata-rata siswa melonjak dari 61,46 menjadi 80,21. Analisis statistik melalui uji paired sample t-test menghasilkan nilai thitung sebesar 19,25 yang melampaui ttabel senilai 2,069, didukung perolehan effect size sebesar 3,93 yang tergolong sangat besar. Simpulan utama menegaskan bahwa bahan ajar "LESTARI" terbukti valid, efektif, dan efisien dalam mendukung pembelajaran berbasis lingkungan yang bermakna. Penggunaan konten lokal seperti ekosistem rawa gambut dan budaya Dayak tidak hanya mengoptimalkan capaian kognitif, tetapi juga berhasil menginternalisasi karakter peduli lingkungan serta kesadaran ekologis siswa sejak usia dini secara berkelanjutan, sistematis, serta holistik bagi keberlangsungan masa depan lingkungan Katingan.